Microplegia in paediatric hearts - Münch, Frank; Kwapil, Nicola; Teske, Andreas; Rueffer, Andre; Dittrich, Sven; Volk, Tilmann; Purbojo, Ariawan (Perfusion-Uk, 2022)
Introduction A basic prerequisite for a good surgical outcome in heart surgery is optimal myocardial protection. However, cardioplegia strategies used in adult cardiac surgery are not directly transferable to infant hearts. Paediatric microplegia, analogous to Calafiore cardioplegia used in adult cardiac surgery, offers the advantage of safe myocardial protection without haemodilution. The use of concentration-dependent paediatric microplegia is new in clinical implementation. Material and methods Paediatric microplegia has been in clinical use in our institution since late 2014. It is applied via an 1/8 inch tube of a S5-HLM roller pump (LivaNova, Italy). As cardioplegic additive, a mixture of potassium (K) 20 mL (2 mmol/mL potassium chloride 14.9% Braun) and magnesium (Mg) 10 mL (4 mmol/mL Mg-sulphate Verla (R) i. v. 50%) is fixed into a syringe-pump (B. Braun, Germany). This additive is mixed with arterial patient blood from the oxygenator in different flow dependent ratios to form an effective cardioplegia. Technique After microplegia application of initially 25 mmol/L K with 11 mmol/L Mg for 2 min, a safe cardioplegic cardiac arrest is achieved, which after release of the coronary circulation, immediately returns to a spontaneous cardiac-rhythm. In the case of prolonged aortic clamping, microplegia is repeated every 20 min with a reduction of the application dose of K by 20% and Mg by 30% (20 mmol/L K; 8.5 mmol/L Mg) and a further reduction down to a maintenance dose (15 mmol/L K; 6 mmol/L Mg) after additional 20 min. The microplegia adapted to the needs of paediatric myocardium is convincing due to its simple technical implementation for the perfusionist while avoiding haemodilution. However, the required intraoperative interval of microplegia of approx. 20 min demands adapted intraoperative management from the surgeon.
CRIS-Team WoS Importer:2022-09-30